Multicultural of Education - Rif'an Syafruddin (CV. ADIBA AISHA AMIRA, 2021)
Multicultural education to apply in the teaching and learning process cannot be separated from planning. Planning for instruction as well as for learning begins with one premise but ends with another. It begins with the idea that teachers need to seek curriculum objectives, usually from the foreign ministry of education or curriculum document publishers